Successful treatment of psoriatic crumbly nails with ustekinumab. Issue 3 (21st April 2019) - Galluzzo, Marco; D'Adamio, Simone; Chimenti, Maria Sole; Teoli, Miriam; Bianchi, Luca; Talamonti, Marina
Abstract: Nail involvement can place a significant burden on patients as a result of functional damage and psychosocial problems, leading to major repercussions on the quality of life. There is strong evidence that nail psoriasis can often be difficult to treat. We report a 69‐year‐old man with severe onychodystrophy, onycholysis, and pain in the hands; he had been previously treated with topical and systemic traditional therapies without satisfactory response. The patient showed multiple severe psoriatic crumbly nails (nail psoriasis severity index [NAPSI] score of 69) and started ustekinumab treatment at standard dosage of 45 mg fl.s.c. After 24 weeks, both nail matrix and nail bed disease showed marked improvement and the patient continued therapy with ustekinumab (NAPSI 0 at week 104). At week 136 (September 2015), the patient had been complaining of hands pain (visual analogue scale pain: 80) and ultrasonographic (US) evaluations found a synovial proliferation with effusion on metacarpophalangeal joints. The patient continued therapy with ustekinumab, adding methotrexate 10 mg fl.s.c/week. In November 2016, the patient showed a remission of symptoms; clinical and US evaluations did not find signs of synovitis. Methotrexate treatment was suspended and currently the patient reached more than 4 years of ustekinumab treatment without sign and symptoms of synovitis.